Post‐fire hydrological response and suspended sediment transport of a terraced Mediterranean catchment. Issue 14 (30th June 2017) - García‐Comendador, Julián; Fortesa, Josep; Calsamiglia, Aleix; Calvo‐Cases, Adolfo; Estrany, Joan
Abstract: In July 2013, a wildfire severely affected the western part of the island of Mallorca (Spain). During the first three post‐fire hydrological years, when the window of disturbance tends to be more open, the hydrological and sediment delivery processes and dynamics were assessed in a representative catchment intensively shaped by terracing that covered 37% of its surface area. A nested approach was applied with two gauging stations (covering 1.2 km 2 and 4.8 km 2 ) built in September 2013 that took continuous measurements of rainfall, water and sediment yield. Average suspended sediment concentration (1503 mg L −1 ) and the maximum peak (33 618 mg L −1 ) were two orders of magnitude higher than those obtained in non‐burned terraced catchments of Mallorca. This factor may be related to changes in soils and the massive incorporation of ash into the suspended sediment flux during the most extreme post‐fire event; 50 mm of rainfall in 15 min, reaching an erosivity of 2886 MJ mm ha −1  h −1 . Moreover, hysteretic counter‐clockwise loops were predominant (60%), probably related to the increased sensitivity of the landscape after wildfire perturbation. Though the study period was average in terms of total annual precipitation (even higher in intensities), minimal runoff (2%) and low sediment yield (6.3 t km −2 y −1 ) illustrated how the intrinsic characteristics of the catchment, i.e. calcareous soils, terraces and the application of post‐fire measures, limited the hydrosedimentary response despite the wildfire impact. Copyright © 2017 John Wiley & Sons, Ltd.